What can traditional Chinese medicine do for adult neurogenesis? - Shen, Wei; Jiang, Ning; Zhou, Wenxia (Frontiers in Neuroscience, 2023)
Adult neurogenesis plays a crucial role in cognitive function and mood regulation, while aberrant adult neurogenesis contributes to various neurological and psychiatric diseases. With a better understanding of the significance of adult neurogenesis, the demand for improving adult neurogenesis is increasing. More and more research has shown that traditional Chinese medicine (TCM), including TCM prescriptions (TCMPs), Chinese herbal medicine, and bioactive components, has unique advantages in treating neurological and psychiatric diseases by regulating adult neurogenesis at various stages, including proliferation, differentiation, and maturation. In this review, we summarize the progress of TCM in improving adult neurogenesis and the key possible mechanisms by which TCM may benefit it. Finally, we suggest the possible strategies of TCM to improve adult neurogenesis in the treatment of neuropsychiatric disorders.